2012
DOI: 10.1016/j.jvs.2012.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular treatment of thoracoabdominal aortic aneurysms

Abstract: Although we have treated a cohort at high operative risk, our midterm results compare favorably with the published series of conventional surgery. Accurate hemodynamic control represented by high-normal perioperative blood pressure seems to protect against severe postoperative complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
101
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(108 citation statements)
references
References 18 publications
7
101
0
Order By: Relevance
“…This rate is in line with other contemporary endovascular series. 7,18,20 To reduce the incidence and impact of SCI, aggressive pre-operative, intra-operative, and post-operative management has been adopted. Stent graft planning aims to routinely maintain LSA and bilateral hypogastric artery perfusion whenever possible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This rate is in line with other contemporary endovascular series. 7,18,20 To reduce the incidence and impact of SCI, aggressive pre-operative, intra-operative, and post-operative management has been adopted. Stent graft planning aims to routinely maintain LSA and bilateral hypogastric artery perfusion whenever possible.…”
Section: Discussionmentioning
confidence: 99%
“…9,20 In this series, 19 ASA IV patients were treated. Both operative and late mortality in this small group were higher compared with patients scoring ASA III or less.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 When hybrid repair techniques, branched and fenestrated prostheses are used, mortality rates of 5.5 to 8.9% are reported, [15][16][17][18] although the fact that long-term follow-up is lacking should be borne in mind.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective study showed the successful implementation of such a protocol with effective reduction in the number of SCI cases [32]. The rate of SCI has been reported to be 3-11% for endovascular repair and is comparable to the rate of open surgery [33,34]. With these adjuncts, the incidence of SCI could be lowered [35][36][37].…”
Section: Current Treatment Concepts General Principlesmentioning
confidence: 99%